Resource misallocation and total factor productivity: Manufacturing firms in South Africa - Carol Newman; John Rand; Mpho Asnath Tsebe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Misallocation of labour and capital can greatly reduce aggregate productivity. In this study, we use tax administrative data to examine the extent of resource misallocation in the South African context. In addition, we zoom in on how different government incentives affect the allocation (or misallocation) of capital and labour across firms, and we quantify the extent to which alleviating these policy-induced distortions would improve productivity for the manufacturing sector in South Africa. We also analyse heterogeneity in the extent of misallocation along the firm size distribution and identify firm size categories where these policy distortions are having the biggest impact on productivity.
Keywords: D24; O4; 330; marginal revenue product; resource misallocation; South Africa; total factor productivity